CONTEMPLATION ET MYTHOSOPHIE: L’AMPHIBOLIE DES PAYSAGES DANS L’ŒUVRE D’ERNST JÜNGER - CÂMPEAN, Flaviu-Victor (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
Contemplation and Mythosophy: the Amphiboly of Landscapes in the Works of Ernst Jünger. Ernst Jünger’s immanent mythology of vitalism hasn’t as yet found its place in Modernity, being regarded as suspect or unworthy of any serious post-metaphysical approach. Nevertheless, its original significance is manifest in the spatial descriptions that deploy a genuine polymorphism of human nature and an archetypal Aesthetics. Jünger’s landscapes thus express at least two different levels of amophiboly that encompass his status as a specific literary figure, apart from both Metaphysics and Deconstruction. His solutions, varying throughout the evolution of his work, aim the enigmatic and unthinkable articulation of Myth and History, the topological frontiers between creative decision and the vertical advent of an injunction, open like a wound towards the Faustian destiny.